25 legendary leadership activities - Garber, Peter R. (HRD Press, 2008)
Find the legendary leader inside you! What is "legendary leadership"? It can be defined simply as leadership that is remembered. These 25 activities are designed to ensure you are remembered as a good - or even great - leader. The number of people in the group you lead or the size of your organization doesn't matter. The book is organized around the qualities and abilities that enable a leader to effectively lead a few people ... a large organization ... or even a nation. Whether you are a new or experienced leader, you will find development activities that cover a wide variety of skills that can help you reach your greatest potential. Do you need to work on dealing with demands on your time? Pacing yourself? Feeling comfortable in all your many different roles? Making difficult decisions? Understanding and capitalizing on your leadership style? You'll find just the right activity here. Sample activities include: How Do You Spend Your Leadership Time; The "Plugged-In" Leader; Managing Sideways; Leading Outside the Box; Leadership Survival Skills; Collaborative Management. The activities couldn't be easier to use. You'll get the purpose of the activity, description of the activity, time allotted, resources required, presentation instructions and a debrief. The 25 handouts - including assessments, questionnaires and charts - make this book even more useful. 25 Legendary Leadership Activities - challenging, fun and a must resource in your legendary leadership journey